Mendorong Pemilu 2019 Berkualitas dan Berintegritas di Provinsi Lampung - Hertanto, Hertanto (Jurnal Analisis Sosial Politik, 2019)
The 2019 General Election (Pemilu) is the first simultaneous election in Indonesia which will simultaneously elect a presidential/vice-presidential candidate, a candidate of the member of the Republic of Indonesia Parliament, the DPD RI or the Indonesian Regional Representative, and the Provincial/Regency/City assembly. Various analyzes predict that the practice of simultaneous elections that will take place is not easy task for Indonesia, it is full of challenges that need to be dealt with, and it has also the potential to create numerous problems. As the result, this is presumably as the complicated election in the world. This study wants to explain how the challenges and potential vulnerability of the 2019 Election in Lampung, and how to anticipate it. The results of the analysis explain that the potential challenges of the 2019 Election are on the quality and integrity of the Lampung’s election especially on the factors of money politics, campaign implementation, usage of state and local government facilities. While the potential weaknesses is based on the predictions of the Republic of Indonesia General Election Supervisory Board (Bawaslu), the 2019 Election vulnerability index in Lampung is under the high category (49.56). Further, based on the 2018 Pilkada Election in Lampung Province, the highest potential vulnerability is in its participation, where the public supervision variable shows a fairly high index and it is followed by the voting right factor (IKP Pilkada 2018). Meanwhile, the dimensions of election organizers have the potential for vulnerability which needs to be anticipated especially in the context of integrity and professionalism of the election organizers. Therefore, based on challenges and vulnerabilities that need to be anticipated, encouraging the active participation of civil society groups such as NGOs, universities, mass media to exercise control over the practice of money politics, campaign funds, and misuse of government facilities and policies. Strengthening the control of civil society will result in a a good quality electoral process, and finally it will result in elections with a high integrity. Pemilihan Umum (Pemilu) 2019 merupakan pemilu serentak pertama di Indonesia yang sekaligus akan memilih calon presiden/wakil presiden, calon anggota DPR RI, DPD RI, dan DPRD Provinsi/Kabupaten/Kota. Berbagai analisis memprediksikan bahwa praktik pemilu serentak ini akan berlangsung tidak mudah, penuh tantangan, dan berpotensi mengalami banyak persoalan. Sehingga ada anggapan bahwa inilah pemilu yang paling rumit di dunia. Kajian ini ingin menjelaskan bagaimana tantangan dan potensi kerawanan Pemilu 2019 di Lampung, serta bagaimana antisipasinya. Hasil analisis menjelaskan bahwa tantangan potensial Pemilu 2019 berkualitas dan berintegritas di Lampung pada faktor politik uang, pelaksanaan kampanye, penggunaan fasilitas negara dan daerah. Sedangkan potensi kerawanan berdasarkan prediksi Badan Pengawas Pemilihan Umum Republik Indonesia (Bawaslu RI) bahwa indeks kerawanan Pemilu 2019 di Lampung termasuk pada kategori yang tinggi (49,56). Berdasarkan IKP Pilkada 2018 di Provinsi Lampung, potensi kerawanan tertinggi terdapat pada dimensi partisipasi, di mana variabel pengawasan masyarakat menunjukkan indeks cukup tinggi dan diikuti variabel hak pilih (IKP Pilkada, 2018). Sementara, pada dimensi penyelenggara pemilu potensi kerawanan yang perlu diantisipasi pada variabel integritas dan profesionalitas penyelenggara. Oleh karena itu, berlandaskan pada tantangan dan kerawanan tersebut perlu diantisipasi dengan mendorong partisipasi aktif kelompok- kelompok masyarakat sipil (NGO, perguruan tinggi, media massa) untuk melakukan kontrol terhadap: praktik politik uang, dana kampanye, serta penyalahgunaan fasilitas dan kebijakan pemerintah sebagai instrumen pemenangan. Penguatan kontrol masyarakat sipil akan menghasilkan proses pemilu yang berkualitas, dan akhirnya akan menghasilkan pemilu yang berintegritas.